Formation of professional competence of qualified workers in vocational education to information and educational environment - Lypska, Larysa (Professional Pedagogics, 2016)
In the article the problem of formation of professional competence of skilled workers in the system of vocational ocvity using information-educational environment. Training and production process of vocational education institution is defined as a deliberate, consciously organized, dynamic interaction teacher, master and apprentice, during which solved socially necessary task of education, training, formation of professional competence and basic competences. The quality of the educational process in vocational education depends on many factors, the main ones include educational environment. Teachers of subjects training can offer students a virtual tour of the production, showing step by step processes that they have to master, show the final result, perspectives for professional development. As a result, it significantly helps students transform an interest profession of motivation for its development. Information and educational environment can be seen on one hand as part of the traditional educational system, and the other as an independent system, aimed at the development of creative activity of students with the use of new information technologies. The main objective information and educational environment of vocational training zakladu- promote student motivation for self-development, self-education by providing the necessary information and resources to ensure open and full access to information. Information and educational environment - is one of the sides of the vocational educational institution, which includes organizational, methodological, technical and software for storing, processing, transmission information and provides quick access to information.